Driving forces for texture transformation in thin Ag films. (15th February 2016) - Ellis, Elizabeth A.; Chmielus, Markus; Lin, Ming-Tzer; Joress, Howie; Visser, Kyle; Woll, Arthur; Vinci, Richard P.; Brown, Walter L.; Baker, Shefford P.
Abstract: The well-known thickness-dependent (111)-to-(100) texture transformation in thin FCC films is usually attributed to a competition between interface and strain energies. In this model, thin films retain their (111) texture due to the lower energy of the (111) interface, while thick films transform to (100) due to the lower stiffness and thus strain energy of a (100) film. However, recent work has called this model into question, suggesting that neither the stress nor the interface energy play a dominant role in texture transformation. We investigated the driving forces involved in this transformation by using a bulge test apparatus to induce different stresses in thin Ag films under identical annealing conditions. In situ synchrotron XRD measurements show the change in texture during annealing, and reveal that applied stresses have no effect on the transformation. Stress analysis shows that differences in driving forces for texture transformation due to applied bulge pressure were significant (≈200 kJ/m 3 ), suggesting that a different, much larger driving force must be responsible. Reduction in defect energy has been proposed as an alternative. However, vacancy and dislocation densities must be exceptionally high to significantly exceed the strain energy and do not provide obvious orientation selection mechanisms. Nanotwins in reported densities are shown to provide greater driving force (≈1000 kJ/m 3 ) and may account for orientation selection. The large difference between the calculated strain and defect energies and the driving force for grain growth (21, 100 kJ/m 3 ) casts doubt on the applicability of a simple thermodynamic model of texture transformation. Graphical abstract: